ASSOCIATION OF FOOT PAIN AND HEEL HEIGHT AMONG HEALTH CARE STUDENTS: http://doi.org/10.46536/jpumhs/2024/14.02.518 - ASSOCIATION OF FOOT PAIN AND HEEL HEIGHT AMONG HEALTH CARE STUDENTS Mansha Devi1, Venti Anmol2, Bahadur Ali3, Faryal4, Anum5, Anchal6, Muhammad Azeem Akhuand7, Imran Ali Memon8, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
BACKGROUND: High heels shoes (HHS) are worn by a lot of women all over the world, Wearing high heels is often a part of women’s style. OBJECTIVES: To determine the frequency of foot pain, the use of different heel heights among healthcare students, and the association between foot pain and heel height. METHODOLOGY: The quantitative cross sectional study was conducted in Sindh from December 2023 to May 2024. 427 health care students participated in the study by means of convenience sampling technique. Data was collected using foot health status questionnaire to measure frequency of foot pain and self-generated questionnaire to determine frequency of wearing heel of different categories among health care students respectively. Data was analyzed through Statistical Package for the Social Sciences (SPSS) Version 21. Demographic data was analyzed by descriptive statics and expressed as mean, standard deviation which was presented in tabulated form. Chi Square test was used to find association between foot pain and heel height. RESULTS: The study sample comprised of 427 health care students mean age of students was 21.7±1.8. Among the participants, 47.5% reported no pain, 24.8% had very mild pain, 61.8% wore flat heels, and 28.6% wore low heels. CONCLUSION: The study found no significant correlation between foot pain and heel height among healthcare students.